Study on Evaluation and proposal to mitigate Environmental Impacts in an enterprise in the Municipality of Jardim, Ceará (Research, Society and Development, 2020)
Civil construction produces several impacts, whether beneficial or adverse, and may be socioeconomic and environmental. Mitigating measures can be applied to alleviate the environmental imbalance, making it necessary to develop materials and techniques to minimize the negative environmental impacts resulting from these activities. It stands out the technologies of brick-cement production, a venture that does not lead to burning in its manufacturing process. There are few studies applied to the evaluation of environmental impacts of this type of enterprise, although it is essential to identify them and seek solutions to minimize the negative effects, a fact that justifies the writing of this article. The objective of this work is the Environmental Impact Assessment in an ecological brick factory in the city of Jardim - CE, through the use of the checklist methodology, to evaluate the positive and negative impacts, as well as to present mitigating measures. The results showed that the project generates more positive than negative impacts, representing 61% and 39%, respectively, and no negative impact reached the phase of studies and projects, while the implementation phase was the one that generated the most impacts.